An enhanced EFQM methodology for evaluating the performance of organization - Sajedi, Mohammad Askari; Mohd Yusuff, Rosnah; Angiz L., Majid Zerafat; Mustafa, Adli; Zulkifli, Norzima; Ismail, Md. Yusof; Gholamzadeh, Mahdi; Mojahed, Majid (Marsland Press, 2013)
Previous studies show that traditional scoring system in EFQM model is not robust and is suffering a problem causing deviation in assessing the performance of an organization. This study aims to establish a realistic scoring system and accurate using one of the MCDM methods. AHP method is used in order to consider the effect of interaction EFQM criteria. Moreover, traditional scoring of EFQM model is used in this analysis. Results show that new scoring system is more efficient than the traditional scoring system. This is because that the traditional scoring system of EFQM is based on additive calculations whereas AHP method considers interaction effects of criteria and sub criteria in EFQM model. Also the efficiency and effectiveness of the new scoring system were confirmed by the data obtained from the performance evaluation of 35 organizations in a case study. The integration EFQM and AHP models can create a new scoring system to help prevent the deviation of organization performance assessment.